AUDIT DELAY, UKURAN KANTOR AKUNTAN PUBLIK, FINANCIAL DISTRES, OPINI AUDIT, DAN UKURAN PERUSAHAAN KLIEN TERHADAP AUDITOR SWITCHING - Tahniatun Naili; Nora Hilmia Primasari (Universitas Pamulang, 2020)
This research is conducted to analyze the influence of audit delay, size of public accountant firm, financial distress, audit opinion and company size of auditor switching. The population in this research is used secondary data from the financial statment of all companies listed in the Indonesia Stock Exchange in 2015-2017 as many 529 companies. This research used purposive sampling method and obtainde 359 companies sample. The data analysis used logistic regression analysis with program SPSS version 20. The result of this research show that size of public accountant firm and audit opinion have negative effect on auditor switching. While audit delay, financial distress and company size have not effect on auditor switching.